THE DEVELOPMENT OF LEARNER’S WORK SHEET (LKPD) IN UNDERSTANDING THE FOLKLORE TEXT BASED ON SOUTH SUMATERA LOCAL WISDOM - Hardayanti, Rika; Nurhayati, Nurhayati; Suhendi, Didi
This study aimed (1) to describe the needs of teachers and seventh grade students at SMP N 1 Indralaya towards LKPD in understanding the folklore text based on South Sumatera local wisdom, (2) to produce prototype LKPD in understanding the folklore text based on South Sumatera local wisdom as the needs of teachers and seventh grade students at SMP N 1 Indralaya, (3) to describe the validity of LKPD in understanding the folklore text based on South Sumatera local wisdom based on the assessment fromthe expert team, (4) to describe the practicality of LKPD in understanding the folklore text based on South Sumatra local wisdom which usedthe experiment of one-to-one evaluation and small group evaluation, and (5) to describe the effectiveness of LKPD in understanding the folklore text based on South Sumatra local wisdom based on field test. The research method and development modified and elaborated the development theories of Gall, Gall, and Borg and the development theories of Tessmer. LKPD produced in this study was in accordance to the needs of learners and teachers. This LKPD had passed a validation test by the three experts includingthe feasibility aspects: material, language, presentation, and chart. Based on the validation of the three experts, it was concluded that LKPD was valid and feasible to be tested with revisions as the expert comments and suggestions. Based on the results of one-to-one and small group tests, LKPD was practical to be used by the learners. Based on the results of field test through pretest and posttest, the mean score of understanding the folklore text of the learners has increased from 61.4063 to 77.4219 (difference of 16.0156). Thus, LKPD of South Sumatera Local Wisdom on the folklore textis effective in improving the ability of learners in understanding the folklore text.